Drug Repurposing Prediction and Validation From Clinical Big Data for the Effective Treatment of Interstitial Lung Disease - Siswanto, Soni; Yamamoto, Hiroki; Furuta, Haruka; Kobayashi, Mone; Nagashima, Takuya; Kayanuma, Gen; Nagayasu, Kazuki; Imai, Yumiko; Kaneko, Shuji (Frontiers in Pharmacology, 2021)
Interstitial lung diseases (ILDs) are a group of respiratory disorders characterized by chronic inflammation and fibrosis of the pulmonary interstitial tissues. Although the etiology of ILD remains unclear, some drug treatments are among the primary causes of ILD. In the present study, we analyzed the FDA Adverse Event Reporting System and JMDC Inc. insurance claims to identify a coexisting drug that reduced the incidence of ILD associated with the use of an anti-arrhythmic agent, amiodarone, and found that the thrombin inhibitor dabigatran prevented the amiodarone-induced ILD in both clinical datasets. In an experimental validation of the hypothesis, long-term oral treatment of mice with amiodarone caused a gradual decrease in body weight caused by respiratory insufficiency. In the lungs of amiodarone-treated mice, infiltration of macrophages and interstitial thickening were observed in parallel with a delayed upregulation of the platelet-derived growth factor receptor  gene. In contrast, co-treatment with dabigatran significantly attenuated these amiodarone-induced changes indicative of ILD. These results suggest that dabigatran is effective in preventing drug-induced ILD. This combinatorial approach of drug repositioning based on clinical big data will pave the way for finding a new treatment with high clinical predictability and a well-defined molecular mechanism.